Question

Use the method for solving homogeneous equations to solve the following differential equation.

(9x^2-y^2)dx+(xy-x^3y^-1)dy=0

solution is F(x,y)=C, Where C= ?

Answer #1

Solve the Homogeneous differential equation
(7 y^2 + 1 xy)dx - 1 x^2 dy = 0
(a) A one-parameter family of solution of the equation is y(x)
=
(b) The particular solution of the equation subject to the
initial condition y(1) =1/7.

Use the method for solving equations of the form
dy/dx=G(ax+by)
to solve the following differential equation.
dy/dx=2sin(4x-2y) ignore lost solutions and give implicit
solution in the form F(x,y)=c

Use the method for solving Bernoulli equations to solve the
following differential equation
dx/dy+5t^7x^9+x/t=0
in the form F(t,x)=c

Solve the equation.
(2x^3+xy)dx+(x^3y^3-x^2)dy=0
give answer in form F(x,y)=c

solve differential equation ((x)2 - xy +(y)2)dx - xydy
= 0
solve differential equation (x^2-xy+y^2)dx - xydy =
0

(61). (Bernoulli’s Equation): Find the general solution of the
following first-order differential equations:(a) x(dy/dx)+y=
y^2+ln(x) (b) (1/y^2)(dy/dx)+(1/xy)=1

solve the differential equation...
(x2-1)(dy/dx)+xy=0

(x-y)dx + (y+x)dy =0 Solve the differential equation

differential equations solve
(2xy+6x)dx+(x^2+4y^3)dy, y(0)=1

solve for y:
1. dy/dx= xe^y separable
2. x(dy/dx)+3y=x^2 when y(5)=0 1st order linear

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 1 minute ago

asked 3 minutes ago

asked 7 minutes ago

asked 8 minutes ago

asked 11 minutes ago

asked 12 minutes ago

asked 15 minutes ago

asked 19 minutes ago

asked 25 minutes ago

asked 26 minutes ago

asked 27 minutes ago

asked 28 minutes ago